Clinicomanometric factors associated with clinically relevant esophagogastric junction outflow obstruction from the Sandhill high‐resolution manometry system. Issue 3 (10th October 2017) - Song, B. G.; Min, Y. W.; Lee, H.; Min, B.‐H.; Lee, J. H.; Rhee, P.‐L.; Kim, J. J.
Abstract: Background: Integrated relaxation pressure (IRP) is a key metric for diagnosing esophagogastric junction outflow obstruction (EGJOO). However, its normal value might be different according to the manufacturer of high‐resolution manometry (HRM). This study aimed to investigate optimal value of IRP for diagnosing EGJOO in Sandhill HRM and to find clinicomanometric variables to segregate clinically relevant EGJOO. Methods: We analyzed 262 consecutive subjects who underwent HRM between June 2011 and December 2016 showing elevated median IRP (> 15 mm Hg) but did not satisfy criteria for achalasia. Clinically relevant subjects were defined as follows: (i) subsequent HRM met achalasia criteria during follow‐up (early achalasia); (ii) Eckardt score was decreased at least two points without exceeding a score of 3 after pneumatic dilatation (variant achalasia); and (iii) significant passage disturbance on esophagogram without structural abnormality (possible achalasia). Key Results: Seven subjects were clinically relevant, including two subjects with early achalasia, four subjects with variant achalasia, and one subject with possible achalasia. All clinically relevant subjects had IRP 20 mm Hg or above. Among subjects (n = 122) with IRP 20 mm Hg or more, clinically relevant group (n = 7) had significantly higher rate of dysphagia (100% vs 24.3%, P < .001) and compartmentalized pressurization (85.7% vs 21.7%, P = .001) compared to clinically non‐relevant group (n = 115). Conclusions & Inferences: Our results suggest that IRP of 20 mm Hg or higher could segregate clinically relevant subjects showing EGJOO in Sandhill HRM. Additionally, if subjects have both dysphagia and compartmentalized pressurization, careful follow‐up is essential. Abstract : Our results suggest that 20 mm Hg is the optimal cut‐off value of integrated relaxation pressure for diagnosing esophagogastric junction outflow obstruction in the Sandhill system. Dysphagia and compartmentalized pressurization on manometry are crucial clinicomanometric factors that can segregate clinically relevant esophagogastric junction outflow obstruction patients.